SOLUSI PERTANIAN MODERN YANG RAMAH LINGKUNGAN DAN EFISIEN (SPRINT) - Galih, Galih (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2024)
Patrolsari Village, located in Arjasari District, Bandung Regency, is currently facing significant challenges due to prolonged drought. The minimal rainfall has caused the agricultural sector, which heavily relies on rainwater, to be neglected. This situation affects not only farmers but also residents who struggle to meet their daily water needs. In response to these conditions, UNINUS students initiated the SPRINT program (Sustainable and Efficient Modern Agriculture Solutions), utilizing hydroponics as an alternative farming method. This program aims to provide solutions for village residents, particularly women farmers and local farmers, to continue farming during the extended drought. Hydroponics, which uses water as a planting medium, offers numerous benefits, including efficiency and positive impacts on mental health. Moreover, this method enables residents to produce fresh and economically valuable vegetables. By implementing simple techniques using recycled materials and organic nutrients from animal manure (KOHE), hydroponics can become a sustainable solution for Patrolsari Village. This article further explores the potential of hydroponics as an environmentally friendly farming solution during the dry season, its benefits, and its application methods in Patrolsari Village.